Long-Term Efficacy of Non-steroid Immunosuppressive Agents in Anti-Muscle-Specific Kinase Positive Myasthenia Gravis Patients: A Prospective Study - Tan, Ying; Shi, Jiayu; Huang, Yangyu; Li, Ke; Yan, Jingwen; Zhu, Li; Guan, Yuzhou; Cui, Liying (Frontiers in Neurology, 2022)
Background and purpose: Anti-muscle-specific kinase (MuSK) positive myasthenia gravis (MG) is characterized by a high relapsing rate, choosing the appropriate oral drug regimen is a challenge. This study aimed to evaluate the efficacy of oral immunosuppressants (IS) in preventing relapse in MuSK-MG. Methods: This prospective cohort observational study included patients with MuSK-MG at Peking Union Medical College Hospital between January 1, 2018, and November 15, 2021. The patients were divided into 2 groups: those with (IS+) or without (IS-) nonsteroid immunosuppressive agents. The primary outcome was relapse at follow up, and log-rank test was used to compare the proportion of maintenance-free relapse between the groups; hazard ratio (HR) was calculated using the Cox proportional hazards models. Results: Fifty-three of 59 patients with MuSK-MG were included in the cohort, fourteen were in the IS+ group, and thirty-nine were in the IS- group. Twenty-four cases in the cohort experienced relapse at least once; the relapse rate was 2/14 (14.3%) in the IS+ group and 22/39 (56.4%) in the IS- group. At the end of follow up, the proportion of maintenance-free relapse was significantly different between the two groups (log-rank χ2=4.94，P=0.02). Of all the potential confounders, only the use of IS was associated with reduced risk of relapse. The HR for relapse among patients in the IS+ group was 0.21 (95%CI 0.05-0.58) and was 0.23 (95%CI 0.05-0.93) in a model adjusted for age, sex, relapse history, highest MGFA and accumulated time of steroid therapy. Conclusions: This study provides evidence that oral nonsteroid immunosuppressive agents may be beneficial in reducing relapse in patients with MuSK-MG.